Hekaleka Foundation Financial Information System Development - Febiyola Wijaya; Monika Handojono; Meidylisa Patty (Jurnal Mantik, 2022)
The use of information technology in the accounting process is recognized as bringing many advantages, especially in terms of practicality, time requirements and the availability of real-time financial information. Various parties involved, both internal and external, who are geographically separated, can access information of the same quality, and can also be involved in financial management. Organizationally, Heka Leka's financial management is carried out by several parties, namely, the executive director, program director, financial advicer, and treasurer. However, it must be acknowledged that the recording and financial reporting that has been carried out has not been carried out properly. As a result, the information supplied has not been able to meet the needs of the parties involved. Therefore, it is necessary to develop a financial management system that allows all stakeholders, both internal and external, to access the resulting information. In addition, information systems can produce financial information that can be relied on by its users. The implementation of the service includes three stages, namely conducting financial report training and how to input financial data to the Malessy, the Hekaleka network and the Hekaleka Foundation management. This training went smoothly and the Hekaleka Foundation provided participants and accommodated the participants' attendance. Even looking for a place to do training, because the Foundation's place didn't allow it to accommodate a large number of people.